Clinical outcomes following inpatient penicillin allergy testing: A systematic review and meta‐analysis. Issue 9 (26th April 2017) - Sacco, K. A.; Bates, A.; Brigham, T. J.; Imam, J. S.; Burton, M. C.
Abstract: Background: A documented penicillin allergy is associated with increased morbidity including length of hospital stay and an increased incidence of resistant infections attributed to use of broader‐spectrum antibiotics. The aim of the systematic review was to identify whether inpatient penicillin allergy testing affected clinical outcomes during hospitalization. Methods: We performed an electronic search of Ovid MEDLINE/PubMed, Embase, Web of Science, Scopus, and the Cochrane Library over the past 20 years. Inpatients having a documented penicillin allergy that underwent penicillin allergy testing were included. Results: Twenty‐four studies met eligibility criteria. Study sample size was between 24 and 252 patients in exclusively inpatient cohorts. Penicillin skin testing (PST) with or without oral amoxicillin challenge was the main intervention described (18 studies). The population‐weighted mean for a negative PST was 95.1% [CI 93.8‐96.1]. Inpatient penicillin allergy testing led to a change in antibiotic selection that was greater in the intensive care unit (77.97% [CI 72.0‐83.1] vs 54.73% [CI 51.2‐58.2], P <.01). An increased prescription of penicillin (range 9.9%‐49%) and cephalosporin (range 10.7%‐48%) antibiotics was reported. Vancomycin and fluoroquinolone use was decreased. Inpatient penicillin allergy testing was associated with decreased healthcare cost in four studies. Conclusions: Inpatient penicillin allergy testing is safe and effective in ruling out penicillin allergy. The rate of negative tests is comparable to outpatient and perioperative data. Patients with a documented penicillin allergy who require penicillin should be tested during hospitalization given its benefit for individual patient outcomes and antibiotic stewardship.